Analisis Penggunaan Ateji pada Lirik Theme Song Game Diabolik Lovers: More Blood (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2018)
Ateji is one of variety in using Japanese letters, especially kanji. Theoretically, there are not many, especially State University of Jakarta, Japanese Department’s Students, who understand what ateji is. Although practically, there are many students who can gave out the example of ateji itself. From this explanation, it could be concluded that State University of Jakarta, Japanese Department Students, still have not understand what is ateji yet. This research is conducted by descriptive qualitative method. This method is used in order to describe the variety of Diabolik Lovers: More Blood’s theme song’s ateji, the reason of using ateji and the semantic expansion in words which using ateji. To collect the data, researcher used library research while for analyzed the data, Shirose’s theory of classifying ateji is used to classify every ateji found in the lyrics. Based on the results, there are 44 ateji which is divided into 4 categories. Those categories are kougo no yomi wo shimesu, gairaigo no yomi wo shimesu, daimeishi and iikaehyougen. Then, in those 44 ateji, four of them are borrowing its letters sound and the rest are borrowing its letters meaning. Research about ateji could be implied in Japanese Linguistic class as knowledge of variety in using Japanese letters, especially kanji, since this research is about the using of ateji which is one of variety in using Japanese letters.